Alterações no metabolismo lipídico hepático em ratos obesos submetidos à derivação duodeno-jejunal - Soares, Gabriela Moreira (2016)
Hypothalamic obesity (HyO) is a severe condition without any effective therapy. Bariatric operations appear as an alternative treatment, but the effects of this procedure are controversial. Here, we investigated the effects of duodenal-jejunal bypass (DJB) upon lipid profile and expression of main genes, protein and transcription factors involved in hepatic lipid metabolism pathways in HyO rats. During the first 5 days of life, male newborn Wistar rats received a subcutaneous injection of monosodium glutamate (MSG) [4 g/kg body weight (BW), HyO group]. Control (CTL) group received saline [1.25 g/kg BW]. At 90 days of age, HyO rats were randomly submitted to DJB or sham operations forming HyO DJB and HyO Sham group, respectively. Six months after DJB, obesity parameters, lipids levels, and expression of genes and protein in the liver were verified. HyO Sham rats displayed obesity, hyperinsulinemia, insulin resistance, hypertryglyceridemic and presented higher free fatty acids (FFA) levels and hepatic triglyceride (TG) content. Also, HyO Sham animals enhanced acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN) and stearoyl-CoA desaturase-1 (SCD-1) mRNA levels and ACC and FASN protein in the liver. Carnitine palmitoyltransferase-1a (CPT-1a) and microsomal TG transfer protein (MTTP) were down-regulated in HyO Sham rats. DJB operation normalized serum insulin, TG and FFA levels and hepatic TG content, without changing obesity in these animals. In addition, DJB reduced mRNA levels of liver pyruvate kinase (LPK), ACC, SCD-1, acyl-CoA oxidase (ACO) and carbohydrate response elemento-binding protein (ChREBP). ACC and FASN protein expression were normalized in HyO DJB animals. DJB reduces de-novo lipogenesis and improves hepatic TG content in HyO DJB rats, indicating that this surgery is efficient in the resolution of nonalcoholic fatty liver disease (NAFLD) in HyO.